212 Mart Movement In Palembang: The Failed Experiment of Islamic Populism - Hafidh, Afdil; Isbah, M. Falikul (RMPI-BRIN, 2023)
The case of blasphemy charges against Basuki Cahaya Purnama, also known as Ahok, in Jakarta in 2017 sparked a wave of mass protests, calling themselves the 212 Movement. Based on various criteria and characteristics, scholars have labeled it as an Islamic populist movement, which later inspired various articulations of the movement in different locations. This article explores the articulation of this movement in the economic field under the name 212 Mart in Palembang, South Sumatra. Using the framework of Social Movement Theory, there are two main findings. First, the 212 Mart movement attempts to articulate the ideology of Islamic populism as the framing of the movement through identity sentiments and the strengthening of the community’s economy. The ideology of Islamic populism positions the Muslim community as socially and economically marginalized. Second, the failure of the experimentation of Islamic populism in the 212 Mart movement is attributed to the weakening of economic opportunities and the structure of political opportunities. Thus, this article has contributed to studying Islamic populism through social movement theory by revealing the failure of the 212 Mart movement in Palembang.